Using mining industry wastewater to obtain Prussian blue analogues-silica monolith hybrids: a key to reduce water pollution - Montesdeoca Arredondo, Kimberly Fernanda (2022)
Materials with hierarchical porosity and functionalized with different metals such as copper (II), zinc (II), iron (II) and iron (III) were synthesized to obtain silica monoliths for the treatment of wastewater from mining extraction. Silica monoliths were synthesized using the high internal phase emulsion method (HIPE). After functionalizing the structure with the metals they were subsequently impregnated with Ferrocyanide or synthetic wastewater from mining extraction, to in situ precipitate Prussian blue analogues (PBA’s) and to reduce the cyanides content in the water. Ferrocyanide impregnation was performed by contact under controlled conditions, while impregnation with wastewater was performed by non-continuous laminar flow. The amount of adsorbed CN was then determined as well as the possible formation of Prussian Blue Analogues (PBA's) inside the monolith in order to obtain materials to be possible used for storage energy (batteries or H2 storage). This possible formation was determined by the characterization of the samples during the functionalization and impregnation phases by XRD, ATR-FTIR, DRS-UV-Vis, magnetic susceptibility measurements, and SEM-EDX. For the functionalization phase, information was obtained from ATRFTIR, EDX and DRS-UV-Vis techniques showing that metals were present in the form of oxides. For the ferrocyanide contact impregnation phase the PBAs were formed in the monolith structure, which was confirmed by ATRFTIR, DRS-UV-Vis XRD, Magnetic susceptibility measurements, and SEM-EDX. For the impregnation phase with synthetic water in laminar flow using the monoliths as microreactors, complexes were formed that are not necessarily PBA and it was observed that the CN concentration decreased at least 30% of initial concentration. This work presents a potential and interesting way to use wastewater to mitigate CN and heavy metal contamination and in turn to manufacture materials that could be used in energy storage.